2018
DOI: 10.1029/2018wr023457
|View full text |Cite
|
Sign up to set email alerts
|

GeoFlood: Large‐Scale Flood Inundation Mapping Based on High‐Resolution Terrain Analysis

Abstract: Recent floods from intense storms in the southern United States and the unusually active 2017Atlantic hurricane season have highlighted the need for real-time flood inundation mapping using high-resolution topography. High-resolution topographic data derived from lidar technology reveal unprecedented topographic details and are increasingly available, providing extremely valuable information for improving inundation mapping accuracy. The enrichment of terrain details from these data sets, however, also brings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 39 publications
2
103
0
Order By: Relevance
“…A number of studies have shown the HAND methodology can produce accurate inundation maps from a known streamflow and carefully created HAND layers (Afshari et al, 2018;Rennó et al, 2008;Rodda, 2005;Zheng et al, 2018b). There has not been, however, an exploration of how errors in the NWM-HAND methodology, and its individual components, might compound and propagate through flood simulation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the HAND methodology can produce accurate inundation maps from a known streamflow and carefully created HAND layers (Afshari et al, 2018;Rennó et al, 2008;Rodda, 2005;Zheng et al, 2018b). There has not been, however, an exploration of how errors in the NWM-HAND methodology, and its individual components, might compound and propagate through flood simulation.…”
Section: Introductionmentioning
confidence: 99%
“…These distances may be evaluated horizontally or vertically using the D flow model with weighted averaging applied where flow is proportioned between multiple grid cells. The D distance down function, calculated vertically with the target grid cells being stream grid cells, may be used to calculate HAND (Zheng, Maidment, et al, ). This D distance down evaluation of HAND differs from earlier HAND approaches (Nobre et al, ; Nobre et al, ) that use D8.…”
Section: Introductionmentioning
confidence: 99%
“…Each reach in the National Hydrography Dataset (NHDPlus medium resolution; McKay et al, ) has a separate forecast discharge, and HAND is used to evaluate rating curves and map inundation for the NHDPlus catchment draining into each reach. In another recent study, Zheng, Maidment, et al () implemented the HAND approach with high‐resolution topographic data derived from light detection and ranging using a geodesic minimization technique to map the streams (Passalacqua et al, ; Sangireddy et al, ). This approach maps streams by selecting a flow path to minimize a metric that is a combination of contributing area, curvature, and distance from NHDPlus (medium resolution) streams.…”
Section: Introductionmentioning
confidence: 99%
“…Papaioannou et al (2015) studied a multicriteria perspective for delineation of potential floodprone areas for the Xerias River watershed, Greece. Zheng et al (2018) performed similar studies on high-resolution terrain analysis for Onion Creek watershed, central Texas.…”
Section: Literature Reviewmentioning
confidence: 99%